THE DEPICTION OF BEAUTY IN NPURE INSTAGRAM CONTENT: A STUDY OF WIDDOWS' THEORY AND KRESS & LEEUWEN'S METAFUNCTIONS - Lerissa Daniela; Andrias Yulianto; Agnes Asnidar Sihura (Faculty of Letters Universitas Balikpapan, 2024)
Social media platforms, such as Instagram, have become prominent spaces for individuals and companies to showcase their daily lives, products, and ideals. Npure, a skincare company, utilizes its Instagram presence to communicate the concept of beauty, frequently featuring women as the main characters in their posts. This study delves into the portrayal of the concept of beauty in Npure's Instagram content, with a focus on the use of women to convey this notion. By employing Widdows' (2018) theory of beauty and Kress and Leeuwen's (2021) metafunctions, a qualitative textual analysis was conducted. Data was obtained through purposive sampling of Npure's Instagram account, and subsequently analyzed within the framework of the aforementioned theories. The findings revealed that the four selected figures depict women with smooth, flawless skin holding a product close to their faces, showcasing luminosity with their smiles. Figure 5, although without a product, also highlights flawless skin. These figures exude youthfulness through cheerful expressions and firm, sag-free facial features, emphasizing beauty with clear skin, bright smiles, and a lack of visible pores or blemishes.